Silver particles

By using silver particles with a specific particle size ratio as the conductive adhesive component, the problem of pressurization during sintering and the problem of low-temperature sintering efficiency is solved, and a sintered body with high density and mechanical strength is achieved.

CN114206526BActive Publication Date: 2025-04-15OSAKA SODA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202080056564.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-02
Filing Date
2020-08-12
Publication Date
2025-04-15
Estimated Expiration
2040-08-12

AI Technical Summary

Technical Problem

The existing conductive adhesives need to be pressurized during sintering, resulting in insufficient mechanical strength, easy cracks and voids, and difficult to sinter at low temperatures, affecting the reliability of electronic components.

Method used

Silver particles A with an average particle size of 50-500 nm and silver particles B with an average particle size of 0.5-5.5 μm are used. The average particle size relationship between the two is 5-11 times. As the conductive adhesive component, it can be sintered at a low temperature even without pressurization, forming a sintered body with high density and mechanical strength.

Benefits of technology

The conductive adhesive sintered at low temperature without pressurization is realized, the density and mechanical strength of the sintered body are improved, and the problems of many voids and insufficient mechanical strength of the sintered body in the prior art are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114206526B_ABST
    Figure CN114206526B_ABST
Patent Text Reader

Abstract

Provided is a novel silver particle which, when used as a conductive adhesive, can be appropriately sintered at a low temperature even when no pressure is applied during sintering of the conductive adhesive, and can form a sintered body having high density and mechanical strength (shear strength). A silver particle comprising: silver particles A having an average particle size in the range of 50 to 500 nm; and silver particles B having an average particle size in the range of 0.5 to 5.5 μm, wherein the average particle size of the silver particles B is 5 to 11 times the average particle size of the silver particles A.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to silver particles, a conductive adhesive, a sintered body of the conductive adhesive, and an electronic component having the sintered body between members. Background Art

[0002] Conductive adhesives, such as adhesive sheets, are bonding materials used in electronic components such as semiconductors, LEDs, and power semiconductors. As bonding methods, bonding using pressurization and heating, or bonding with a substrate by sintering using heating or the like under non-pressurization is generally known. In recent years, the development of bonding materials using non-pressurization methods has been promoted from the perspective of simplicity and efficiency of the manufacturing process.

[0003] As a non-pressurized bonding material, one example is a conductive adhesive containing epoxy resin. This bonding material is used by curing epoxy resin under low temperature treatment, which can inhibit the generation of voids and improve the bonding strength with the substrate (Patent Document 1). However, the epoxy resin itself becomes a resistor, so the resulting electrical conductivity and thermal conductivity become low.

[0004] On the other hand, the development of silver particles as a bonding material that does not contain thermosetting resins such as epoxy resins has been promoted in recent years. Silver particles have the characteristic that they can be easily sintered by heat treatment at low temperature for a short time. For example, Patent Document 2 discloses a metal paste, in which a solid component containing silver particles and a solvent are kneaded, and the solid component is composed of silver particles containing more than 30% of silver particles with a particle size of 100 to 200 nm based on the number of particles, and further, the silver particles constituting the solid component are bonded with an amine compound having a total number of carbon atoms of 4 to 8 as a protective agent. According to this metal paste, silver particles can be sintered in a low temperature range, and on this basis, a sintered body with low resistance and a sintered body with excellent thermal conductivity can be formed.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2010 / 18712

[0008] Patent Document 2: Japanese Patent Application Publication No. 2015-159096 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In the field of conductive adhesives, in order to reduce the voids (improve the density) of a sintered body obtained by coating and sintering a conductive adhesive on a component (such as a substrate used in an electronic component, a semiconductor chip, etc.), pressurization is generally performed during sintering (pressure is, for example, about 10 to 30 MPa). The conductive adhesive is sintered while being pressurized, thereby reducing the voids in the sintered body. It should be noted that when there are many voids in the sintered body, the mechanical strength (shear strength) becomes insufficient, or cracks and defects are easily generated in the sintered body, and there are problems in reliability. On the other hand, there are also problems such as damage to the component coated with the conductive adhesive due to pressurization during sintering, and the need for special equipment for pressurization. In addition, when the sintered body is formed on a semiconductor chip having a complex structure, there is also the problem that the conductive adhesive cannot be pressurized.

[0011] Therefore, in recent years, there has been a demand for the development of a conductive adhesive that can form a sintered body having high density and mechanical strength (shear strength) even without applying pressure during sintering of the conductive adhesive.

[0012] Furthermore, although conductive adhesives are generally sintered at a sintering temperature of about 300° C., there is a need for conductive adhesives that can be sintered at a lower temperature (for example, a sintering temperature of 250° C. or less).

[0013] The above problems can be solved if a new conductive adhesive can be provided which can be sintered appropriately at low temperature even without applying pressure during sintering of the conductive adhesive and can form a sintered body having high density and mechanical strength (shear strength).

[0014] Under such circumstances, the main object of the present invention is to provide a novel silver particle which, when used as a conductive adhesive, can be appropriately sintered at a low temperature even without applying pressure during sintering of the conductive adhesive, and can form a sintered body having high density and mechanical strength (shear strength). Furthermore, the present invention also aims to provide a conductive adhesive containing the silver particle, a sintered body of the conductive adhesive, and an electronic component having the sintered body between components.

[0015] Means for solving problems

[0016] The present inventors have conducted intensive research to solve the above-mentioned problems. As a result, it was found that when relatively small silver particles having an average particle size within a predetermined range and relatively large silver particles having an average particle size within a predetermined range are used, and the average particle sizes of the large silver particles and the small silver particles are set to a specific relationship, when the silver particles are used as a conductive adhesive, even if no pressure is applied during sintering of the conductive adhesive, it is possible to appropriately sinter at a low temperature, and further, a sintered body with high density and mechanical strength (shear strength) can be formed. The present invention was completed based on such knowledge and further repeated research.

[0017] That is, the present invention provides the following aspects of the invention.

[0018] Item 1. A silver particle, characterized in that it comprises:

[0019] Silver particles A having an average particle size in the range of 50 to 500 nm; and

[0020] Silver particles B having an average particle size in the range of 0.5 to 5.5 μm,

[0021] The silver particles satisfy the relationship that the average particle size of the silver particles B is 5 to 11 times the average particle size of the silver particles A.

[0022] Item 2. The silver particles according to Item 1, wherein

[0023] The mass ratio of the silver particles A to the silver particles B is in the range of 1:9 to 9:1.

[0024] Item 3. The silver particles according to Item 1 or 2, wherein

[0025] An amine compound is attached to the surface of the silver particles A.

[0026] Item 4. The silver particles according to any one of Items 1 to 3, wherein

[0027] The silver particles include silver particles with a particle size less than 50 nm.

[0028] Item 5. A conductive adhesive, characterized in that:

[0029] The method comprises the silver particles according to any one of items 1 to 4 and a solvent.

[0030] Item 6. A sintered body of the conductive adhesive according to Item 5.

[0031] Item 7. An electronic component in which members are joined together via the sintered body according to Item 6.

[0032] Item 8. A method for producing a sintered body, characterized in that:

[0033] The method comprises the step of sintering the conductive adhesive according to item 5 at a temperature of 200° C. to 250° C.

[0034] Item 9. A method for manufacturing an electronic component in which components are joined by a sintered body, comprising:

[0035] A step of disposing the conductive adhesive described in item 5 between the components; and

[0036] A step of sintering the conductive adhesive at a temperature of 200° C. to 250° C.

[0037] Effects of the Invention

[0038] According to the present invention, when a conductive adhesive is prepared, it is possible to provide novel silver particles that can be appropriately sintered at a low temperature even without applying pressure during sintering of the conductive adhesive, and can form a sintered body having high density and mechanical strength (shear strength). Furthermore, according to the present invention, it is also possible to provide a conductive adhesive containing the silver particles, a sintered body of the conductive adhesive, and an electronic component having the sintered body between components. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 is a SEM image of silver particle A1.

[0040] Figure 2 is a SEM image of silver particle A2.

[0041] Figure 3 is a SEM image of silver particle B1.

[0042] Figure 4 is a SEM image of silver particle B2.

[0043] Figure 5 is a SEM image of silver particle B3.

[0044] Figure 6 This is a TG-DTA chart obtained for the silver particles A1 and A2. DETAILED DESCRIPTION

[0045] The silver particles of the present invention are characterized in that they include silver particles A having an average particle size in the range of 50 to 500 nm and silver particles B having an average particle size in the range of 0.5 to 5.5 μm, and the average particle size of the silver particles B is 5 to 11 times the average particle size of the silver particles A. The silver particles of the present invention have such characteristics, and therefore, can provide novel silver particles that can be appropriately sintered at a low temperature and can form a sintered body having high density and mechanical strength (shear strength) even when the silver particles are used as a conductive adhesive without applying pressure during sintering of the conductive adhesive.

[0046] The following is a detailed description of the silver particles, the conductive adhesive, the sintered body of the conductive adhesive, and the electronic component having the sintered body between components of the present invention. It should be noted that in this specification, the numerical values ​​connected by "~" refer to the numerical range including the numerical values ​​before and after "~" as the lower limit and upper limit. When multiple lower limits and multiple upper limits are recorded separately, any lower limit and upper limit can be selected and connected by "~".

[0047] 1. Silver particles

[0048] The silver particles of the present invention are particles containing silver, and include silver particles A and silver particles B having different average particle sizes. The average particle size of the silver particles A is in the range of 50 to 500 nm. In addition, the average particle size of the silver particles B is in the range of 0.5 to 5.5 μm. Furthermore, the relationship that the average particle size of the silver particles B is 5 to 11 times the average particle size of the silver particles A is satisfied. That is, for example, when the average particle size of the silver particles A is a lower limit of 50 nm, the average particle size of the silver particles B is in the range of 0.5 to 0.55 μm. In addition, for example, when the average particle size of the silver particles A is an upper limit of 500 nm, the average particle size of the silver particles B is in the range of 2.5 to 5.5 μm.

[0049] The average particle size of the silver particles A only needs to be in the range of 50 to 500 nm. From the viewpoint of further appropriately achieving the effect of the present invention, the lower limit is preferably 60 nm or more, and the upper limit is preferably 300 nm or less, more preferably 250 nm or less, and further preferably 200 nm or less. Preferred ranges include 50 to 300 nm, 50 to 250 nm, 50 to 200 nm, 60 to 300 nm, 60 to 250 nm, and 60 to 200 nm.

[0050] In addition, the average particle size of the silver particles B only needs to be in the range of 0.5 to 5.5 μm. From the viewpoint of further appropriately achieving the effect of the present invention, the lower limit can be preferably 0.6 μm or more, and the upper limit can be preferably 3.0 μm or less, more preferably 2.5 μm or less, and further preferably 2.0 μm or less. The preferred ranges include 0.5 to 3.0 μm, 0.5 to 2.5 μm, 0.5 to 2.0 μm, 0.6 to 3.0 μm, 0.6 to 2.5 μm, and 0.6 to 2.0 μm.

[0051] In the present invention, the average particle size of the silver particles is a volume-based average particle size measured for 200 randomly selected particles using image analysis software (e.g., Macview (manufactured by MOUNTECH Co. Ltd.)) for the SEM image. It should be noted that the SED mode (secondary electron detector) is used in the observation, and the lateral width range of 1 to 20 μm is observed at an acceleration voltage of 20 kV and an observation magnification of 5000 to 30000 times. It should be noted that for the longitudinal direction of the SEM image, the width is set to include more than 200 (usually, about 200 to 300) silver particles in the range of 1 to 20 μm in lateral width. In addition, the volume-based average particle size is a value measured by assuming that the particles observed in the SEM image are spherical with their diameters. The specific measurement method is described in the examples.

[0052] In the silver particles of the present invention, the average particle size of the silver particles B satisfies the relationship of 5 to 11 times the average particle size of the silver particles A. From the viewpoint of further preferably achieving the effect of the present invention, the average particle size of the silver particles B is preferably 8 to 11 times the average particle size of the silver particles A, and more preferably 9 to 11 times.

[0053] In the silver particles of the present invention, the mass ratio of the silver particles A to the silver particles B (silver particles A:silver particles B) is preferably in the range of 1:9 to 9:1, more preferably in the range of 7:3 to 3:7, and further preferably in the range of 6:4 to 4:6. In the silver particles of the present invention, the silver particles A and the silver particles B are dominantly contained, and the total content thereof is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, particularly preferably 98% by mass or more, and may be 100% by mass.

[0054] The silver particles of the present invention may include silver particles having a particle size of less than 50 nm. However, from the viewpoint of further appropriately achieving the effect of the present invention, the proportion of silver particles having a particle size of less than 50 nm is, for example, less than 30%, preferably less than 20%, and more preferably less than 10%, based on the number of silver particles. Similarly, the silver particles of the present invention may include silver particles having a particle size greater than 5.5 μm. However, from the viewpoint of further appropriately achieving the effect of the present invention, the proportion of silver particles having a particle size greater than 5.5 μm is, for example, less than 30%, preferably less than 20%, and more preferably less than 10%, based on the number of silver particles. It should be noted that the particle size referred to herein refers to the volume-based particle size, which is calculated by the aforementioned particle size measurement method. The number ratio of the specific particles is measured by 200 silver particles using image analysis software (Macview).

[0055] In addition, the silver particles of the present invention preferably have multiple exothermic peaks observed in the thermogravimetric differential thermal analysis in the range of 120 to 250°C. Specifically, it is preferred that at least one exothermic peak in the thermogravimetric differential thermal analysis is observed between 120 and 150°C (usually 1), and at least one (usually 1 or 2) is observed between 160 and 250°C. In addition, the weight loss rate of the dry powder of the silver particles of the present invention when heated from 30°C to 500°C by thermogravimetric differential thermal analysis is preferably 1.5% by weight or less, more preferably 0.05 to 1.3% by weight. The method of thermogravimetric differential thermal analysis is as follows.

[0056] <Thermogravimetric differential thermal analysis (TG-DTA)>

[0057] First, prepare air-dried silver particles. For example, when obtaining silver particles from a conductive adhesive for analysis, 2 g of methanol is added to each 1 g of the conductive adhesive to fully disperse the silver particles, and then the silver particles are filtered and air-dried to obtain a dry powder of silver particles as the analysis object. The TG-DTA of the dry powder of the silver particles is measured using a thermogravimetric differential thermal analyzer (e.g., HITACHIG300 AST-2). The measurement conditions are set as atmosphere: air, measurement temperature: 30-500°C, and heating rate: 10°C / min. From the obtained TG-DTA graph, the exothermic peak caused by the binding of the silver particles in the TG-DTA analysis and the weight reduction rate when heated from 30°C to 500°C due to thermal analysis are obtained.

[0058] The content of silver contained in the silver particles of the present invention is preferably 95% by mass or more, more preferably 98% by mass or more.

[0059] From the viewpoint of achieving the effects of the present invention more suitably, the silver particles are preferably surface-treated. That is, the silver particles of the present invention are preferably surface-treated silver particles.

[0060] More specifically, in the silver particles of the present invention, the amine compound is preferably attached to the surface of the silver particles A. In addition, the amine compound may be attached to the surface of the silver particles B. The amine compound may be attached to the surface of the silver particles to form a protective layer. In the silver particles of the present invention, the amine compound is preferably attached so that the average particle size is set to the above-mentioned specific range.

[0061] The amine compound is not particularly limited, but is preferably an alkylamine from the viewpoint of further appropriately achieving the effect of the present invention. The alkylamine is not particularly limited, but preferably an alkylamine having an alkyl group with 3 to 18 carbon atoms, and more preferably an alkylamine having an alkyl group with 4 to 12 carbon atoms.

[0062] Preferred specific examples of the alkylamine include ethylamine, n-propylamine, isopropylamine, 1,2-dimethylpropylamine, n-butylamine, isobutylamine, sec-butylamine, tert-butylamine, isopentylamine, tert-pentylamine, 3-pentylamine, n-pentylamine, n-hexylamine, n-heptylamine, n-octylamine, 2-octylamine, 2-ethylhexylamine, n-nonylamine, n-aminodecane, n-aminoundecane, n-dodecylamine, n-tridecylamine, 2-tridecylamine, n-tetradecylamine, and n-tetradecylamine. Alkylamine, n-pentadecylamine, n-hexadecylamine, n-heptadecylamine, n-octadecylamine, n-oleylamine, N-ethyl-1,3-diaminopropane, N,N-diisopropylethylamine, N,N-dimethylaminopropane, N,N-dibutylaminopropane, N,N-dimethyl-1,3-diaminopropane, N,N-diethyl-1,3-diaminopropane, N,N-diisobutyl-1,3-diaminopropane, N-lauryldiaminopropane, etc. Further, dibutylamine as a secondary amine, cyclopropylamine, cyclobutylamine, cyclopropylamine, cyclohexylamine, cycloheptylamine, cyclooctylamine, etc. as cyclic alkylamines can also be exemplified. Among these, from the viewpoint of further suitably achieving the effect of the present invention, n-propylamine, isopropylamine, cyclopropylamine, n-butylamine, isobutylamine, sec-butylamine, tert-butylamine, cyclobutylamine, n-pentylamine, n-hexylamine, cyclohexylamine, n-octylamine, 2-ethylhexylamine, n-dodecylamine, n-oleylamine, N,N-dimethyl-1,3-diaminopropane, N,N-diethyl-1,3-diaminopropane are preferred, and n-butylamine, n-hexylamine, cyclohexylamine, n-octylamine, n-dodecylamine, N,N-dimethyl-1,3-diaminopropane, N,N-diethyl-1,3-diaminopropane are more preferred. Amine compounds may be used alone or in combination of two or more.

[0063] The amount of the amine compound attached to the silver particles of the present invention is not particularly limited, but is preferably 1.5% by mass or less, more preferably 1.3% by mass or less, based on the mass of the silver particles as 100% by mass, and is preferably 0.05% by mass or more as the lower limit. Similarly, the amount of the amine compound attached to the silver particles A and B is also preferably 1.5% by mass or less, more preferably 1.3% by mass or less, based on the mass of the silver particles A and B as 100% by mass, and is preferably 0.05% by mass or more as the lower limit. The content of the amine compound attached to the silver particles can be measured by thermogravimetric differential thermal analysis.

[0064] In addition, fatty acids, hydroxy fatty acids, etc. may be attached to the surface of the silver particles. As fatty acids, there are no particular restrictions, and fatty acids having preferably 3 to 18 carbon atoms in the alkyl group, and more preferably 4 to 18 carbon atoms in the alkyl group, can be cited. Preferred specific examples of fatty acids include acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, 2-ethylhexanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, α-linolenic acid, etc. In addition, as specific examples of fatty acids, cyclic alkyl carboxylic acids such as cyclohexanecarboxylic acid can also be cited. In addition, as hydroxy fatty acids, compounds having 3 to 24 carbon atoms and having one or more (e.g., one) hydroxyl groups can be used. Examples of hydroxy fatty acids include 2-hydroxydecanoic acid, 2-hydroxydodecanoic acid, 2-hydroxytetradecanoic acid, 2-hydroxyhexadecanoic acid, 2-hydroxyoctadecanoic acid, 2-hydroxyeicosanoic acid, 2-hydroxydocosanoic acid, 2-hydroxytricosanoic acid, 2-hydroxytetracosanoic acid, 3-hydroxyhexanoic acid, 3-hydroxyoctanoic acid, 3-hydroxynonanoic acid, 3-hydroxydecanoic acid, 3-hydroxyundecanoic acid, 3-hydroxydodecanoic acid, 3-hydroxytridecanoic acid, 3-hydroxytetradecanoic acid, 3-hydroxyhexadecanoic acid, 3-hydroxyheptadecanoic acid, 3-hydroxyoctadecanoic acid, ω-hydroxy-2-decenoic acid, ω-hydroxypentadecanoic acid, ω-hydroxyheptadecanoic acid, ω-hydroxyeicosanoic acid, ω-hydroxydocosanoic acid, 6-hydroxyoctadecanoic acid, ricinoleic acid, 12-hydroxystearic acid, and [R-(E)]-12-hydroxy-9-octadecenoic acid. Among them, hydroxy fatty acids having 4 to 18 carbon atoms and having one hydroxyl group other than the ω position (particularly the 12 position) are preferred, and ricinoleic acid and 12-hydroxystearic acid are more preferred. The fatty acid and hydroxy fatty acid may be used alone or in combination of two or more.

[0065] In the silver particles of the present invention, the amount of fatty acids and hydroxy fatty acids attached is appropriately adjusted in the same manner as the amine compounds. The specific amount of fatty acids and hydroxy fatty acids attached is not particularly limited. The mass of the silver particles is set to 100 mass%, preferably 1.5 mass% or less, more preferably 1.3 mass% or less, and the lower limit is preferably 0.01 mass% or more. Similarly, the amount of fatty acids and hydroxy fatty acids attached to the silver particles A and B is also set to 100 mass%, preferably 1.5 mass% or less, more preferably 1.3 mass% or less, and the lower limit is preferably 0.01 mass% or more. The content of fatty acids and hydroxy fatty acids attached to the silver particles can be measured by thermogravimetric differential thermal analysis.

[0066] It should be noted that, as long as the silver particles of the present invention satisfy the above-mentioned average particle size, amine compounds, fatty acids, and hydroxy fatty acids may be used in combination, and other compounds different from these may also be attached to the surface of the silver particles. It is particularly preferred that an amine compound is attached to the surface of the silver particles of the present invention.

[0067] When the silver particles of the present invention are made into a conductive adhesive, the shear strength of the sintered body obtained by heating the conductive adhesive at 200°C is preferably 73 MPa or more, more preferably 77 MPa or more, and further preferably 80 MPa or more. It should be noted that the upper limit of the shear strength is, for example, 200 MPa or less. In addition, when the silver particles of the present invention are made into a conductive adhesive, the shear strength of the sintered body obtained by heating the conductive adhesive at 250°C is preferably 70 MPa or more, more preferably 72 MPa or more, and further preferably 75 MPa or more. It should be noted that the upper limit of the shear strength is, for example, 200 MPa or less. The method for measuring the shear strength of the sintered body is as follows. Specifically, it can be measured by the method described in the examples.

[0068] <Shear strength>

[0069] First, prepare a substrate with 0.5 μm electroless silver plating applied on a copper plate. A conductive adhesive (silver particle dispersion of 90% by mass and 10% by mass of Texanol) is evenly applied on the substrate (the surface with silver plating) in a manner that the coating thickness becomes 50 μm. Furthermore, a silicon wafer (size 2 mm×2 mm) with gold plating applied to the back side (the surface in contact with the conductive adhesive) is stacked on the coating to obtain a laminate. Next, a dryer (circulating type) is used to heat the obtained laminate under the sintering conditions of 60 minutes at a specified sintering temperature (200°C or 250°C), and each conductive adhesive between the substrate and the silicon wafer is sintered to produce 9 laminates in which the substrate and the silicon wafer are joined via a sintered body. For the obtained laminated bodies, a load was applied to the sintered body at 0.120 mm / s using a bonding tester (Japanese original text of "bonding tester": Bond Tester) (e.g., SS30-WD manufactured by Seishin Shoji) at room temperature, and a bare die shear test (Japanese original text of "bare die shear test": Diesel Tester) was performed on each laminated body to measure the maximum load at break. The maximum load thus obtained was divided by the bonding area to obtain the shear strength value. It should be noted that the measurement result is the average value of 9 gold-plated silicon wafers for which the shear strength was measured.

[0070] In addition, when the silver particles of the present invention are made into a conductive adhesive, the density of the sintered body obtained by heating the conductive adhesive at 200°C is preferably 80% or more, more preferably 83% or more. It should be noted that the upper limit of the density is, for example, 95% or less. In addition, when the silver particles of the present invention are made into a conductive adhesive, the density of the sintered body obtained by heating the conductive adhesive at 250°C is preferably 83% or more, more preferably 85% or more. It should be noted that the upper limit of the density is, for example, 97% or less. The method for measuring the density of the sintered body is as follows. Specifically, it can be measured by the method described in the examples.

[0071] <Density>

[0072] In the same manner as described in the "Shear Strength" column, a laminate in which the substrate and the silicon wafer are joined via a sintered body is obtained. Next, the sintered body and the laminate are resin-embedded with an epoxy resin (e.g., manufactured by Buehler Ltd.), and the resin is allowed to stand for 24 hours to allow the resin to cure. Next, the resin-embedded laminate is cut with a precision low-speed cutting machine (e.g., TechCut4 manufactured by ALLIED Corporation), and cross-section grinding is performed using an ion milling machine (e.g., IM4000PLUS manufactured by Hitachi High-Tech Corporation) (e.g., manufactured by Hitachi High-Tech Corporation). It should be noted that the cross-section grinding is performed at a discharge voltage of 1.5 kV, an acceleration voltage of 6 kV, and an argon gas flow rate of 0.07 cm 3 / min, ±30° swing to irradiate ion beam to implement. The cross section of the sintered body obtained by cross-section grinding was observed with a scanning electron microscope to obtain a SEM image. During the observation, the SED mode (secondary electron detector) was used to observe the range of lateral width of 60μm at an accelerating voltage of 20kV and a field of view of 2000 times. It should be noted that for the longitudinal direction of the SEM image, the longitudinal width of the sintered layer of silver is set to be greater than 10μm and less than 200μm. The reason is that when the sintered layer of silver is less than 10μm, it is possible to damage the mechanical strength in terms of the characteristics of the joint body. In addition, when it is greater than 200μm, the bulkiness of the laminate becomes higher, so it is assumed that degassing during sintering is difficult to occur uniformly, which is disadvantageous from the perspective of reliability. In the calculation of density, the obtained SEM image is converted into a two-level tone of white and black by using binarization software (Imagej) to convert the light and dark images, and the density is calculated by the following relationship.

[0073] Density (%) = sintered silver area (number of white pixels) ÷ total sintered body area {sintered silver area (number of white pixels) + pore area (number of black pixels)} × 100

[0074] <Resistivity>

[0075] A conductive adhesive (silver particle dispersion containing 90% by mass of silver particles and 10% by mass of Texanol) is uniformly applied on a polyimide film in a size of 2 mm × 60 mm × 50 μm in thickness, and calcined at a predetermined temperature (200° C. or 250° C.) for 60 minutes to obtain a sintered body. Next, the resistance value of the sintered body is measured at room temperature using a resistance meter (e.g., HIOKI RM3548), and the specific resistance (volume resistance) value is determined based on the value obtained by measuring the actual film thickness using a micrometer. It should be noted that the specific resistance value is the average value of the values ​​obtained by measuring 4 locations of the sintered body.

[0076] In addition, when the silver particles of the present invention are made into a conductive adhesive, the resistivity of the sintered body obtained by heating the conductive adhesive at 200°C is preferably 3.5μΩ·cm or less, more preferably 3.2μΩ·cm or less, and further preferably 3.0μΩ·cm or less. It should be noted that the lower limit of the resistivity is, for example, 2.0μΩ·cm or more. In addition, when the silver particles of the present invention are made into a conductive adhesive, the resistivity of the sintered body obtained by heating the conductive adhesive at 250°C is preferably 3.2μΩ·cm or less, more preferably 3.0μΩ·cm or less. It should be noted that the lower limit of the resistivity is, for example, 1.8μΩ·cm or more. The method for determining the resistivity of the sintered body is as described in the aforementioned <Resistivity> column, and specifically, it can be determined by the method described in the examples.

[0077] <Gap>

[0078] The SEM image of the sintered body is obtained in the same manner as the determination of the above-mentioned <density>. For the SEM image binarized using Imagej, the image analysis type particle size distribution measurement software (Macview) (manufactured by MOUNTECH Co. Ltd.) is used for image processing (by automatically reading the color difference, the void part of the binarized image is analyzed as particles), and the voids of the sintered body are assumed to be spherical, and the number average size of the voids is calculated. At this time, the specific surface area of ​​the sintered body is calculated from the surface area per unit volume of the above-mentioned sphere. It should be noted that the void part refers to the pore part generated by degassing and particle growth, which is different from pores and cracks. The pore part refers to a substance with a diameter of more than 50nm and less than 10μm. Holes with a size of more than 10μm are called pores and cracks, and the void part is converted except for it.

[0079] In addition, in the silver particles of the present invention, when the conductive adhesive is prepared, the voids of the sintered body obtained by heating the conductive adhesive at 200° C. have, for example, the following characteristics. It should be noted that the sintered body is formed by the method described in the above-mentioned <Shear Strength> column. The number average size of the voids is, for example, 0.3 to 1.0 μm. The specific surface area of ​​the voids is, for example, 0.2 to 1.0 μm.2 The number average size was calculated by the aforementioned image processing method using Macview.

[0080] 2. Method for producing silver particles

[0081] An example of the method for producing the silver particles of the present invention is shown below.

[0082] First, a composition for producing silver particles (composition for preparing silver particles) is prepared. Specifically, a silver compound as a raw material of silver particles, and an amine compound attached to the surface of the silver particles as needed, and a solvent are prepared. From the viewpoint of further appropriately realizing the effect of the present invention, preferred silver compounds include silver nitrate, silver oxalate, etc., and silver oxalate is particularly preferred. It should be noted that as a solvent, the same substances as those exemplified as solvents in the conductive adhesive described later can be exemplified. Then, these components are mixed to obtain a composition for preparing silver particles. The proportion of each component in the composition is appropriately adjusted. For example, the content of silver oxalate in the composition is preferably set to about 20 to 70% by mass relative to the total amount of the composition. In addition, if an amine compound is attached to the surface of the silver particles, the content of the amine compound is preferably set to about 5% to 55% by mass relative to the total amount of the composition. In addition, if a fatty acid is attached to the surface of the silver particles, the content of the fatty acid is preferably set to about 0.1% to 20% by mass relative to the total amount of the composition. When the hydroxy fatty acid is attached to the surface of the silver particles, the content of the hydroxy fatty acid is preferably about 0.1% by mass to 15% by mass based on the total amount of the composition.

[0083] It should be noted that silver particles may be temporarily synthesized using a composition for preparing silver particles adjusted so that the content of the amine compound etc. is outside the above range, and the type and adhesion amount of the amine compound etc. may be adjusted by the method described below so as to achieve the above properties (substitution of the amine compound).

[0084] In addition, the mixing means of the components is not particularly limited, and the components can be mixed using a general-purpose device such as a mechanical stirrer, a magnetic stirrer, a vortex mixer, a planetary mill, a ball mill, a three-roll mill, a pipeline mixer, a planetary mixer, a dissolver, etc. In order to avoid the temperature of the composition rising due to the influence of the heat of dissolution and friction heat during mixing, and the start of the thermal decomposition reaction of the silver particles, it is preferred to mix while suppressing the temperature of the composition to, for example, 60° C. or less, particularly 40° C. or less.

[0085] Next, the composition for preparing silver particles is subjected to a reaction in a reaction vessel, usually a reaction by heating, so that a thermal decomposition reaction of the silver compound occurs to generate silver particles. During the reaction, the composition may be introduced into a preheated reaction vessel, or the composition may be introduced into the reaction vessel and then heated.

[0086] The reaction temperature can be any temperature at which the thermal decomposition reaction proceeds and silver particles are generated, and for example, about 50 to 250° C. can be mentioned. In addition, the reaction time can be appropriately selected according to the desired average particle size and the composition of the corresponding composition. As the reaction time, for example, 1 minute to 100 hours can be mentioned.

[0087] Since the silver particles generated by the thermal decomposition reaction are obtained as a mixture containing unreacted raw materials, it is preferred to purify the silver particles. As a purification method, a solid-liquid separation method, a precipitation method using the difference in specific gravity between the silver particles and unreacted raw materials such as an organic solvent, etc. can be cited. As a solid-liquid separation method, filter filtration, centrifugal separation, cyclone, or decanter methods can be cited. In order to facilitate the handling during purification, the mixture containing the silver particles can be diluted with a low boiling point solvent such as acetone and methanol to adjust its viscosity.

[0088] The average particle size of the obtained silver particles can be adjusted by adjusting the composition of the silver particle production composition and the reaction conditions.

[0089] Method for replacing and adjusting amine compound on the surface of silver particles

[0090] By the aforementioned method, temporarily synthesized silver particles (with amine compounds attached to the surface) are prepared and dispersed in a solvent. As the solvent, the same substances as those exemplified as solvents to be compounded in the conductive adhesive described later can be exemplified. Next, other amine compounds are added in an amount ranging from 0.1 to 5 times the mass of the silver particles, and a stirring process is applied at room temperature to 80°C for 1 minute to 24 hours, thereby being able to replace the type of amine compounds attached to the surface of the silver particles, or adjust the amount of attachment. The silver particles replaced with amine compounds can be recovered by the aforementioned solid-liquid separation method, etc.

[0091] 3. Conductive adhesive

[0092] The conductive adhesive of the present invention is characterized by comprising the silver particles of the present invention and a solvent. By including the solvent, the fluidity is improved, and the conductive adhesive of the present invention can be easily arranged in a desired location. The details of the silver particles of the present invention are as described above.

[0093] The solvent is not particularly limited as long as it can disperse the silver particles, but preferably contains a polar organic solvent. Examples of the polar organic solvent include ketones such as acetone, acetylacetone, and methyl ethyl ketone; ethers such as diethyl ether, dipropyl ether, dibutyl ether, tetrahydrofuran, and 1,4-dioxane; 1,2-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,2-hexanediol, 1,6-hexanediol, 1,2-pentanediol, 1,5-pentanediol, 2-methyl-2,4-pentanediol, 3-methyl-1,5-pentanediol, 1,2- Glycols such as octanediol, 1,8-octanediol, 2-ethyl-1,3-hexanediol; glycerol; linear or branched alcohols having 1 to 5 carbon atoms, cyclohexanol, 3-methoxy-3-methyl-1-butanol, 3-methoxy-1-butanol; fatty acid esters such as ethyl acetate, butyl acetate, ethyl butyrate, ethyl formate, Texanol; polyethylene glycol, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, triethylene glycol monomethyl ether, Glycol dimethyl ether, tetraethylene glycol dimethyl ether, 3-methoxybutyl acetate, ethylene glycol monobutyl ether, ethylene glycol monobutyl ether acetate, ethylene glycol monohexyl ether, ethylene glycol monooctyl ether, ethylene glycol mono-2-ethylhexyl ether, ethylene glycol monobenzyl ether, diethylene glycol monomethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether, diethylene glycol monobutyl ether acetate, diethylene glycol monohexyl ether, diethylene glycol mono-2-ethylhexyl propylene glycol, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, tripropylene glycol monopropyl ether, tripropylene glycol monobutyl ether and other diols or diol ethers; N,N-dimethylformamide; dimethyl sulfoxide; terpenes such as pineol; acetonitrile; γ-butyrolactone; 2-pyrrolidone; N-methylpyrrolidone; N-(2-aminoethyl)piperazine, etc. Among these, from the viewpoint of more preferably achieving the effects of the present invention, preferred are linear or branched alcohols having 3 to 5 carbon atoms, 3-methoxy-3-methyl-1-butanol, 3-methoxy-1-butanol, diethylene glycol monobutyl ether, diethylene glycol monobutyl ether acetate, diethylene glycol monohexyl ether, diethylene glycol mono-2-ethylhexyl ether, terpineol, and Texanol.

[0094] In addition to polar organic solvents, the solvent may further include non-polar or hydrophobic solvents. As non-polar organic solvents, linear, branched, or cyclic saturated hydrocarbons such as hexane, heptane, octane, nonane, decane, 2-ethylhexane, and cyclohexane; alcohols such as linear or branched alcohols with more than 6 carbon atoms; aromatic compounds such as benzene, toluene, and benzonitrile; halogenated hydrocarbons such as dichloromethane, chloroform, and dichloroethane; methyl n-amyl ketone; methyl ethyl ketoxime; triacetin, etc. Among these, saturated hydrocarbons and linear or branched alcohols with more than 6 carbon atoms are preferred, and hexane, octane, decane, octanol, decanol, and dodecanol are more preferred. The solvent may be used alone or in combination of two or more.

[0095] In the case of containing both polar organic solvent and non-polar organic solvent, the ratio of polar organic solvent is preferably 5 volume % or more, more preferably 10 volume % or more, and further more preferably 15 volume % or more relative to the total amount of solvent. In addition, it can be set to 60 volume % or less, or 55 volume % or less, or 50 volume % or less. The solvent may also be composed of polar organic solvent only. When the conductive adhesive of the present invention contains a large amount of polar organic solvent like this, the dispersibility of silver particles is also good.

[0096] In the conductive adhesive of the present invention, the proportion of the solvent is not particularly limited, but is preferably 20% by mass or less, more preferably about 5% by mass to 15% by mass.

[0097] The content of the silver particles contained in the conductive adhesive of the present invention is preferably 80% by mass or more, more preferably 85% by mass or more.

[0098] The conductive adhesive of the present invention can be produced by a method including the step of mixing the silver particles of the present invention and a solvent.

[0099] In the method for producing the conductive adhesive of the present invention, the silver particles of the present invention produced in the solvent in the method for producing the silver particles of the present invention described above may be used together with the solvent as the conductive adhesive of the present invention.

[0100] 4. Sintered body of conductive adhesive

[0101] The sintered body of the conductive adhesive of the present invention is obtained by sintering the conductive adhesive of the present invention described in detail in the above-mentioned "2. Conductive adhesive". In the sintered body of the conductive adhesive of the present invention, the components (amine compounds, etc.) attached to the surface of the silver particles and the solvent are mostly separated by the high heat during sintering, and the sintered body is substantially composed of silver.

[0102] There is no particular limitation on the sintering temperature. From the viewpoint of appropriately sintering at low temperature and improving the shear strength and density of the obtained sintered body, for example, 250°C or less, preferably about 150°C to 250°C, and more preferably about 200°C to 250°C can be cited. From the same viewpoint, the sintering time can be preferably about 0.4 hours to 2.0 hours, and more preferably about 0.5 hours to 1.2 hours. In the present invention, the silver particles contained in the conductive adhesive have a characteristic of containing silver particles A with an average particle size in the range of 50 to 500 nm and silver particles B with an average particle size in the range of 0.5 to 5.5 μm, and the average particle size of the silver particles B is 5 to 11 times the average particle size of the silver particles A. Therefore, even if the conductive adhesive is not pressurized during sintering, it can be appropriately sintered at a low temperature of 250°C or less, and a sintered body with high density and mechanical strength (shear strength) can be formed. Therefore, it is not necessary to pressurize the conductive adhesive of the present invention during sintering. That is, the conductive adhesive of the present invention can be suitably used for applications in which it is used without pressurization during sintering. It should be noted that the conductive adhesive of the present invention can also be pressurized during sintering, and the pressure in the case of pressurization is, for example, about 10 to 30 MPa. Sintering can be carried out in an atmosphere such as air, an inert gas (nitrogen, argon), etc. There are no particular restrictions on the sintering means, and examples include an oven, a hot air drying furnace, an infrared drying furnace, laser irradiation, flash lamp irradiation, microwaves, etc.

[0103] The sintered body of the present invention preferably satisfies at least one of the shear strength, density, and resistivity values ​​shown in the column "1. Silver particles". The measurement methods thereof are as described in the columns "Shear strength", "Density", and "Resistivity".

[0104] 5. Electronic components

[0105] The electronic component of the present invention has a portion where components are bonded together using the sintered body of the present invention. That is, the electronic component of the present invention is obtained by placing the conductive adhesive of the present invention described in detail in the aforementioned "2. Conductive adhesive" between components of the electronic component (for example, between components included in a circuit), sintering the conductive adhesive, and bonding the components together.

[0106] As described above, the sintered body of the present invention has high density and shear strength, so the shear strength between components in the electronic component having the sintered body is also high. In addition, the specific resistance value of the electronic component of the present invention can also be made low.

[0107] Example

[0108] The present invention will be described in more detail in the following examples, but the present invention is not limited thereto.

[0109] The details of each component used in Examples and Comparative Examples are as follows.

[0110] Silver oxalate ((COOAg) 2 ) was synthesized by the method described in Japanese Patent No. 5574761.

[0111] ·N,N-Diethyl-1,3-diaminopropane (manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0112] · n-Hexylamine (carbon number 6, manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0113] ·Ricinoleic acid (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0114] 1-Butanol (manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0115] ·Methanol (manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0116] ·Ethylene glycol (manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0117] ·Texanol (manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0118] <Synthesis of Silver Particles A>

[0119] (1) Silver particles A1 (average particle size 68 nm)

[0120] Into a 50 mL glass centrifugal precipitation tube with a magnetic stirrer, ricinoleic acid (2.34 g), N,N-diethyl-1,3-diaminopropane (203 g), and 1-butanol (375 g) were added, stirred for about 1 minute, and then silver oxalate (250 g) was added and stirred for about 10 minutes, thereby obtaining a composition for preparing silver particles A1. Thereafter, these glass centrifugal precipitation tubes were vertically set on a hot stirrer (HHE-19G-U manufactured by Koike Precision Machinery Co., Ltd.) with an aluminum block, stirred at 40°C for 30 minutes, and further stirred at 90°C for 30 minutes. After cooling, the magnetic stirrer was removed, and 15 g of methanol was added to each composition. After stirring with a vortex mixer, a centrifugal precipitation operation was performed at 3000 rpm (about 1600×G) for 1 minute using a centrifugal separator (CF7D2 manufactured by Hitachi Industries, Ltd.), and the centrifugal precipitation tube was tilted to remove the supernatant. The steps of adding 15 g of methanol, stirring, centrifuging, and removing the supernatant were repeated twice to recover silver particles.

[0121] Next, using the obtained silver particle dispersion (methanol solution), n-hexylamine was added in an amount three times the mass of the silver particles, and stirred at room temperature for 4 hours. After stirring, the magnetic stirrer was removed, 15 g of methanol was added to each composition, and after stirring with a vortex mixer, a centrifugal precipitation operation was performed at 3000 rpm (about 1600×G) for 1 minute using a centrifugal separator (Hitachi Industries, Ltd. CF7D2), and the centrifugal precipitation tube was tilted to remove the supernatant. The steps of adding 15 g of methanol, stirring, centrifugal separation, and removing the supernatant were repeated twice to recover silver particles A1 (average particle size 68 nm) in which N,N-diethyl-1,3-diaminopropane attached to the surface of the silver particles was replaced with n-hexylamine.

[0122] (2) Silver particles A2 (average particle size 181 nm)

[0123] Into a 50 mL glass centrifugal precipitation tube with a magnetic stirrer, ricinoleic acid (6.25 g), N,N-diethyl-1,3-diaminopropane (203 g), and 1-butanol (187.5 g) were added, stirred for about 1 minute, and then silver oxalate (250 g) was added and stirred for about 10 minutes, thereby obtaining a composition for preparing silver particles A2. Thereafter, these glass centrifugal precipitation tubes were vertically set on a hot stirrer (HHE-19G-U manufactured by Koike Precision Machinery Co., Ltd.) with an aluminum block, stirred at 40°C for 30 minutes, and further stirred at 90°C for 30 minutes. After cooling, the magnetic stirrer was removed, and 15 g of methanol was added to each composition. After stirring with a vortex mixer, a centrifugal precipitation operation was performed at 3000 rpm (about 1600×G) for 1 minute using a centrifugal separator (CF7D2 manufactured by Hitachi Industries, Ltd.), and the centrifugal precipitation tube was tilted to remove the supernatant. The steps of adding 15 g of methanol, stirring, centrifuging, and removing the supernatant were repeated twice to recover silver particles.

[0124] Next, using the obtained silver particle dispersion (methanol solution), n-hexylamine was added in an amount three times the mass of the silver particles, and stirred at room temperature for 4 hours. After stirring, the magnetic stirrer was removed, 15 g of methanol was added to each composition, and after stirring with a vortex mixer, a centrifugal precipitation operation was performed at 3000 rpm (about 1600×G) for 1 minute using a centrifugal separator (Hitachi Industries CF7D2), and the centrifugal precipitation tube was tilted to remove the supernatant. The steps of adding 15 g of methanol, stirring, centrifugal separation, and removing the supernatant were repeated twice to recover silver particles A2 (average particle size 181 nm) in which N,N-diethyl-1,3-diaminopropane was replaced with n-hexylamine.

[0125] <Silver particles B>

[0126] As silver particles B1 (average particle size: 0.65 μm), product name AG2-1C manufactured by DOWA ELECTRONICS MATERIALS CO., LTD. was used.

[0127] As silver particles B2 (average particle size: 1.88 μm), product name AG3-1F manufactured by DOWA ELECTRONICS MATERIALS CO., LTD. was used.

[0128] As silver particles B3 (average particle size: 2.21 μm), product name AG4-8F manufactured by DOWA ELECTRONICS MATERIALS CO., LTD. was used.

[0129] The silver particles A1, A2, B1, B2, and B3 were observed using a scanning electron microscope (obtaining a SEM image), measured for average particle size (volume-based average particle size), measured for particle size distribution, and measured by TG-DTA under the following conditions.

[0130] <Observation using an electron microscope>

[0131] A scanning electron microscope (SEM (JSM-IT500HR manufactured by JEOL Ltd.)) was used to obtain SEM images of the silver particles A1, A2, B1, B2, and B3. Figure 1 The SEM image of silver particles A1 is shown in Figure 2 The SEM image of silver particles A2 is shown in Figure 3 The SEM image of silver particles B1 is shown in Figure 4 The SEM image of the silver particles B2 is shown in FIG. Figure 5 ] A SEM image of silver particles B3 is shown in FIG.

[0132] <Measurement of average particle size (volume-based average particle size) and particle size distribution (D10 to D100)>

[0133] For each SEM image (lateral width 1 to 20 μm) obtained in the aforementioned <Observation using an electron microscope>, the volume-based average particle size and particle size distribution of 200 randomly selected particles were measured using image analysis software (Macview (manufactured by MOUNTECH Co. Ltd.)). For the longitudinal direction of the SEM image, the range of lateral width 1 to 20 μm was observed. It should be noted that for the longitudinal direction of the SEM image, the width is set to include more than 200 (usually about 200 to 300) silver particles in the range of lateral width 1 to 20 μm. It should be noted that the volume-based average particle size is a value measured by assuming that the particles observed in the SEM image are spherical with their diameter. The results are shown in Tables 1 and 2.

[0134] [Table 1]

[0135] Silver particles A1 Silver Particles A2 Silver particles B1 Silver particles B2 Silver particles B3 Volume-based average particle size 68nm 181nm 0.65μm 1.88μm 2.21μm

[0136] [Table 2]

[0137]

[0138] <Thermogravimetric differential thermal analysis (TG-DTA measurement)>

[0139] The silver particles A1 and A2 were measured using TG-DTA. Specifically, first, a solvent (Texanol) was mixed with silver particles A1 and silver particles A2 in the same manner as in the <Manufacture of Conductive Adhesive> described later to prepare silver particle dispersions with a concentration of 90% by mass. Next, 2 g of methanol was added to 1 g of each silver particle dispersion, and after sufficient dispersion, the silver particles were filtered out and air-dried to obtain a dry powder of silver particles. The TG-DTA of the obtained dry powder of silver particles was measured using HITACHI G300AST-2. The measurement conditions were set as atmosphere: air, measurement temperature: 30 to 500°C, and heating rate: 10°C / min. Based on the obtained TG-DTA graph, the weight reduction rate when heated from 30°C to 500°C was obtained by thermal analysis. The results are shown in Table 3.

[0140] In addition, the silver particles A1 and silver particles A2 were mixed with solvents (Texanol) to prepare silver particle dispersions with a concentration of 90% by mass. Each silver particle dispersion was used for the measurement of the main exothermic peak in TG-DTA analysis using HITACHIG300 AST-2. The measurement conditions were atmosphere: air, measurement temperature: 30 to 500°C, and heating rate: 10°C / min. The resulting TG-DTA graph is shown in Figure 6 . Figure 6 Table 3 shows the exothermic peak temperatures of the respective silver particles.

[0141] [Table 3]

[0142]

[0143] <Manufacturing of conductive adhesive>

[0144] Silver particles A, silver particles B, and a solvent (Texanol) were mixed to obtain the composition shown in Table 4 to prepare a conductive adhesive. Specifically, first, Texanol equivalent to 10% by mass was added to silver particles A1, silver particles A2, silver particles B1, silver particles B2, and silver particles B3, respectively, to prepare silver particle dispersions with a concentration of 90% by mass (silver particle dispersion A1, silver particle dispersion A2, silver particle dispersion B1, silver particle dispersion B2, and silver particle dispersion B3, respectively). During the mixing, MAZERUSTAR manufactured by Kurabo Industries Ltd. was used to mix in a secondary stirring priority mode. Next, each silver particle dispersion and Texanol were mixed to obtain the composition shown in Table 4, thereby obtaining conductive adhesives having the compositions of Examples 1-2 and Comparative Examples 1-4.

[0145] [Table 4]

[0146]

[0147] The units of the numerical values ​​recorded for silver particles A, silver particles B, and solvents in Table 4 are parts by mass. It should be noted that, in the conductive adhesives of Examples 1 and 2 and Comparative Examples 1 to 4, when the number of particles is recorded as 100%, 10% or less of particles having a particle size of less than 50 nm are included. In the measurement of particles smaller than 50 nm, for each SEM image (lateral width 1 to 20 μm) obtained in the aforementioned <Observation using an electron microscope>, the volume particle size of 200 randomly selected particles is measured using image analysis software (Macview (manufactured by MOUNTECH Co. Ltd.)), and the number ratio contained therein is calculated. For the longitudinal direction of the SEM image, the width (range of 1 to 20 μm) containing more than 200 silver particles in the lateral width range of 1 to 20 μm is set.

[0148] <Manufacturing of sintered body (sintering temperature 200°C)>

[0149] First, prepare a substrate with 0.5 μm electroless silver plating applied on a copper plate. A conductive adhesive (silver particle dispersion of 90% by mass and 10% by mass of Texanol) is evenly applied on the substrate (the surface with silver plating) in a manner that the coating thickness becomes 50 μm. Furthermore, a silicon wafer (size 2 mm×2 mm) with gold plating applied to the back side (the surface in contact with the conductive adhesive) is stacked on the coating to obtain a laminate. Next, a dryer (circulating type) is used to heat the obtained laminate under the sintering conditions of 60 minutes at a specified sintering temperature (200°C or 250°C), and each conductive adhesive between the substrate and the silicon wafer is sintered to produce 9 laminates in which the substrate and the silicon wafer are joined via a sintered body.

[0150] In addition, for reference, the silver particle dispersions A1, A2, B1, and B2 prepared in the aforementioned <Manufacture of Conductive Adhesive> (to silver particles A1, A2, B1, and B2, respectively, 10% by mass of Texanol was added to make each silver particle dispersion at a concentration of 90% by mass) were used as conductive adhesives (as shown in Table 5, respectively, Comparative Examples 5 to 8), and sintered bodies were similarly manufactured.

[0151] Various physical properties of the sintered bodies obtained from the conductive adhesives of Examples 1-2 and Comparative Examples 1-8 were measured under the following measurement conditions.

[0152] <Mechanical strength of sintered body (shear strength)>

[0153] The obtained laminate was subjected to a bare die shear test at room temperature using a bonding tester (SS30-WD manufactured by Seishin Shoji) to apply a load to the sintered body at a speed of 0.120 mm / s, and the maximum load at break was measured. The maximum load thus obtained was divided by the bonding area to obtain the shear strength value. It should be noted that the measurement result is the average value of the 9 gold-plated silicon wafers for which the shear strength was measured. The measurement results of the shear strength are shown in Table 5.

[0154] <Density of sintered body>

[0155] Each sintered body and the aforementioned laminate were resin-embedded with epoxy resin (manufactured by Buehler Ltd.) and allowed to stand for 24 hours to cure the resin. Next, the resin-embedded sintered body was cut with a precision low-speed cutting machine TechCut4 (manufactured by ALLIED Corporation) and cross-sectioned for 3 hours using an ion milling machine (IM4000PLUS) (manufactured by Hitachi High-Tech Corporation). It should be noted that the cross-section grinding was performed at a discharge voltage of 1.5 kV, an acceleration voltage of 6 kV, and an argon gas flow rate of 0.07 cm 3 / min, ±30° swing to irradiate the ion beam. The cross section of the sintered body obtained by cross-section grinding was observed using a scanning electron microscope JSM-IT500HR (manufactured by JEOL) to obtain a SEM image. It should be noted that during the observation, the SED mode (secondary electron detector) was used to observe the range of lateral width of 60μm at an acceleration voltage of 20kV and a field of view of 2000 times. It should be noted that for the longitudinal direction of the SEM image, the longitudinal width of the sintered layer of silver was set to a range of more than 10μm and less than 200μm. In the calculation of the density, the obtained SEM image was converted into a two-level tone of white and black using the binary software "image J", and the density was calculated using the following relationship. The results of the density measurement are shown in Table 5.

[0156] Density (%) = sintered silver area (number of white pixels) ÷ total sintered body area {sintered silver area (number of white pixels) + pore area (number of black pixels)} × 100

[0157] <Specific resistance value of sintered body>

[0158] The conductive adhesive (silver particle dispersion of 90 mass % silver particles and 10 mass % Texanol) was uniformly coated on the polyimide film in a manner of 2 mm × 60 mm × coating thickness of 50 μm, and calcined at a specified temperature (200°C or 250°C) for 60 minutes to obtain a sintered body. Next, the resistance value of the sintered body was measured by a two-terminal measurement method using a resistance meter (HIOKI RM3548) at room temperature, and the specific resistance (volume resistance) value was calculated based on the value obtained by measuring the actual film thickness with a micrometer. It should be noted that the specific resistance value is the average value of the values ​​obtained by measuring 4 parts of the sintered body. The results of the specific resistance value measurement are shown in Table 5.

[0159] [Table 5]

[0160]

[0161] <Voids in sintered body (sintering temperature 200℃)>

[0162] For each SEM image binarized using "Image j" obtained in the above <Observation using an electron microscope>, image processing was performed using image analysis type particle size distribution measurement software (Macview) (manufactured by MOUNTECH Co. Ltd.) (by automatically reading the color difference, the void portion of the binarized image was analyzed as particles), and the number average size and specific surface area of ​​the voids in the sintered body were calculated. The results are shown in Table 6. It should be noted that the number average size referred to here is obtained by assuming that the voids are spheres and analyzing them using image analysis software (Macview), and the specific surface area value is obtained by calculating the surface area per unit volume of the above spheres.

[0163] [Table 6]

[0164]

[0165] <Manufacturing of sintered body (sintering temperature 250°C)>

[0166] For each conductive adhesive of Examples 1 and 2, a sintered body was obtained in the same manner as in the above-mentioned <Manufacture of sintered body (sintering temperature 200°C)>, except that the sintering temperature was set to 250°C. Furthermore, for the obtained sintered body, the shear strength, density, and specific resistance value were measured in the same manner as in the above-mentioned <Mechanical strength (shear strength) of sintered body>, <Density of sintered body>, and <Specific resistance value of sintered body>. The results are shown in Table 7.

[0167] [Table 7]

[0168]

[0169] <Voids in sintered body (sintering temperature 250°C)>

[0170] In the same manner as in the above-mentioned <Observation using an electron microscope>, the SEM images of each sintered body obtained in <Manufacturing of sintered body (sintering temperature 250°C)> were obtained, and image processing was performed using the image analysis type particle size distribution measurement software (Macview) (manufactured by MOUNTECH Co. Ltd.) (by automatically reading the color difference, analyzing the void part of the binary image as particles), and the number average size and specific surface area of ​​the voids in the sintered body were calculated. The results are shown in Table 8. It should be noted that the number average size referred to here is obtained by assuming that the voids are spheres and analyzing them through the image analysis software (Macview), and the specific surface area value is obtained by calculating the surface area per unit volume of the above-mentioned spheres.

[0171] [Table 8]

[0172]

Claims

1. A silver particle, characterized in that: Include: Silver particles A having a volume-based average particle size in the range of 50 to 500 nm; and Silver particles B having a volume-based average particle size in the range of 0.5 to 5.5 μm, The silver particles satisfy the relationship that the volume-based average particle size of the silver particles B is 5 to 11 times the volume-based average particle size of the silver particles A, The mass ratio of the silver particles A to the silver particles B is in the range of 3:7 to 7:3, Among them, the method for determining the volume-based average particle size is: using the secondary electron mode of SEM, observing silver particles at an acceleration voltage of 20 kV and an observation magnification of 5000~30000 times, using image analysis software to randomly select 200 particles from the observed SEM image with a lateral width of 1~20 μm, and assuming each particle to be a sphere with its diameter to obtain the volume-based average particle size.

2. The silver particles according to claim 1, wherein The volume-based average particle size of the silver particles A is in the range of 50 to 250 nm.

3. The silver particles according to claim 1 or 2, wherein An amine compound is attached to the surface of the silver particles A.

4. The silver particles according to claim 1 or 2, wherein The silver particles include silver particles with a particle size less than 50 nm.

5. A conductive adhesive, characterized in that: The method comprises the silver particles according to any one of claims 1 to 4 and a solvent.

6. A sintered body of the conductive adhesive according to claim 5.

7. An electronic component in which members are joined together by the sintered body according to claim 6.

8. A method for producing a sintered body, characterized in that: The method comprises the step of sintering the conductive adhesive according to claim 5 at a temperature of 200° C. to 250° C.

9. A method for manufacturing an electronic component in which components are joined by sintered bodies, comprising: a step of disposing the conductive adhesive according to claim 5 between the members; and A step of sintering the conductive adhesive at a temperature of 200° C. to 250° C.

Citation Information

Patent Citations

  • Manufacture of bun with ingredient

    JP1980074761A

  • Silver paste excellent in low-temperature sintering property and method of producing silver paste

    JP2015159096A

  • Conductive adhesive and LED substrate using the same

    WO2010018712A1

  • Electrically conductive adhesives

    CN103108932A

  • Silver particle coating composition

    CN106232268A